Role Play in Health Education Health and Clean Lifestyle Behavior Through Hand Washing - Maria Floriana Ping; Fransiska Novita Sari; Muh Taufiqurrahman (Salus Publica: Journal of Community Service, 2023)
Hand washing is very effective in preventing disease and reducing the spread of bacteria when eating. Correct hand washing behavior is influenced by the level of knowledge possessed by the community, especially elementary school children. The importance of knowledge about PHBS, especially hand washing during school-age children which is considered to have the potential to be an agent of change for the community and the surrounding environment. Community service activities for health education PHBS hand washing through the role play method were carried out for students in grades 1 & 2 of Elementary School 014 Sungai Bawang Cultural Village. The results of the activity show that there is an increase in knowledge about hand washing in students so that the knowledge they already have can be maintained and improved through application in everyday life through the supervision of teachers and parents